The Earthquake Disaster in Türkiye: A Review from Child and Adolescent Psychiatry Perspective - Yasemin İmrek; Gülen Güler Aksu (Düzce Tıp Fakültesi Dergisi, 2023)
The earthquake has long-lasting various mental and behavioral effects on children and adolescents. The aim of this review was to discuss the nature and extent of psychiatric problems, management options, and the process of organizing psychological interventions for affected children. Individuals show a range of physically, emotionally, and cognitively healthy responses that can help them cope with the aftermath of a disaster. Psychiatric symptoms such as acute stress reactions, post-traumatic stress disorder, depression, anxiety disorder, increased risk of suicide, sleep disorders, substance use disorders, and psychotic disorders may develop in some children. Comorbidities and sub-clinical syndromes are also common. There are many risk factors and protective factors in the development of mental disorders. Close follow-up of children at high risk and interventions for psychosocial support may prevent the development of mental disorders. It is very important to start the intervention at the earliest period. The psychological impacts of young disaster victims can be addressed by skilled local volunteers, medical professionals, and educators in primary health care programs. With the nation's overall social and economic recovery, children can recover more quickly from traumatic experiences.